(untitled) (Research, Society and Development, 2025)
This article aims to propose a control technique that enables the simultaneous control of active and reactive power through a structure based on the dq transformation, which also facilitates power flow reversal. The ModularMultilevel Converter (MMC) has proven to be a promising alternative for High Voltage Direct Current (HVDC) transmission systems. In such applications, semiconductor devices must be connected in series due to their limited voltage ratings, and the MMC architecture addresses this requirement by employing multiple cascaded submodules. Additionally, the MMC is capable of synthesizing output waveforms with low harmonic distortion, eliminating the need for bulky and costly filters traditionally required in HVDC systems. Despite not using AC filters, the converter still requires arm inductors, which may increase overall system cost. The control strategy proposed in this work demonstrated excellent performance, producing low-distortion waveforms even with reduced switching frequency. This reduction decreases semiconductor stress and enhances converter efficiency. Furthermore, the implemented capacitor-voltage balancing algorithm operated effectively, maintaining stable capacitor voltages. However, the update period of this algorithm must be carefully selected, as shorter update intervals help minimize voltage imbalance but may increase the effective switching frequency.